E-Government services: Improving employment services in Dumai City - Afrizal, Dedy; Wallang, Muslimin; Hijeriah, E Maznah; Erlianti, Dila; Yusuf, Irfan Murtadho (Universitas Merdeka Malang, 2023)
E-government in Dumai City is a manifestation of the responsibility of the Dumai local government to improve the quality of services that are presented electronically based on websites. The development of e-government is an innovation that is carried out in developing effective and efficient government administration. The Dumai City Manpower and Transmigration Office is one of the government agencies that runs e-government services in serving communities and companies to obtain employment information. The system formed to serve the job seeker community is known as the Employment Information System (SINAKER). Empirically, this system was implemented to answer several complaints from people who wanted speed of information related to job opportunities for the community. Services that are carried out manually are still not optimal, so a good step is taken to help the community openly. This article aims to look at the process of e-government services in Dumai City which aims to assist the government in maximizing service to the community, so that people can access information on job opportunities that can be accessed via the internet. The research findings that there are 3 (three) aspects in the development of e-Government through the created system. Various suggestions were given to the government to improve its services to the public.